Mengungkap Konsep Bilangan Prima dalam Surat Al-Kautsar - Mubaroh, Umi Azizatul; Mujib, Mujib; Syazali, Muhamad (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
This study requires to use a qualitative model, while for the type of research, using Content Analysis. Content analysis is a model used to examine the documentation data in the form of text, images, symbols, and so forth. A research technique for making inferences that can be replicated and valid data with the context. As a technique of research, the content analysis includes specific procedures for processing the scientific data with the aim of providing knowledge, open new horizons and presenting the facts. Assessment of the linkages primes 3 includes a discussion on the relationship with the meaning and also lafadznya, apart from Al-Kautsar consists of three paragraphs, including the font used and unused in the letter, the difference between the two is 6 (multiples of prime numbers 3), for the number of repetitions of letters obtained 111.111.111.123.444.510 numbers (multiples of primes 3), in a letter lafadz هللاproduce numbers 15 and 1,040 (multiples of primes 3), the sequence of letters and the number of letters in the Qur'an produced 114 108 numbers (multiples of primes 3), correlation beginning and end of the letter gives the figure 1.515 (multiples of primes 3), and the number of repetitions of letters in each verse, second verse generate numbers 1.111.111.224, 1.111.111.122 generate numbers second paragraph, and paragraph the third 1.111.111.125 produce numbers which are all multiples of primes 3.